2008
DOI: 10.1038/gene.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

Congenic strains displaying similar clinical phenotype of arthritis represent different immunologic models of inflammation

Abstract: Proteoglycan (PG)-induced arthritis (PGIA) is an autoimmune inflammatory disease controlled by multiple genes in the murine genome. BALB/c.DBA/2 congenic strains carrying four major PGIA chromosome loci were immunized, and positions of loci on chromosomes 3, 7, 8, and 19 (loci Pgia26, Pgia21, Pgia4, and Pgia12, respectively) were confirmed. Each congenic strain exhibited a different pattern of regulation of clinical and immunologic features of PGIA, and these features were significantly influenced by gender. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Naïve BALB/c mice rarely develop spontaneous inflammation in synovial joints (Adarichev et al, 2008; Farkas et al, 2009). BALB/c females infected with B. melitensis for 26 weeks exhibited multiple skeletal involvement with inflammatory and non-inflammatory features.…”
Section: Resultsmentioning
confidence: 99%
“…Naïve BALB/c mice rarely develop spontaneous inflammation in synovial joints (Adarichev et al, 2008; Farkas et al, 2009). BALB/c females infected with B. melitensis for 26 weeks exhibited multiple skeletal involvement with inflammatory and non-inflammatory features.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Chromosomal positions of these loci were confirmed in congenic strains. 26 The initial size of the Pgia26 locus was 60 Mbp of the DBA/2-homozygous ‘core,’ and it could have been larger (up to 64 Mbp) if flanking BALB/c-homozygous areas were taken into consideration (Figure 1; Table 1). Similarly, the Pgia23/Pgia12 locus was 46 Mbp in size, 58 Mbp with the flanking regions.…”
Section: Resultsmentioning
confidence: 82%
“…Since Pgia26 was found initially to be a ‘female-specific’ locus, and the Pgia12 locus was ‘male-specific’ when linkage analysis of the F2 hybrid population was performed, 26,27 we immunized both females and males of the congenic/subcongenic strains along with wild-type (WT) BALB/c females ( n = 87) and males ( n = 54). When all of the data from the clinical phenotypes of all WT, congenic and subcongenic strains were analyzed together (389 total animals for chr3 and 357 for chr19), the gender effect of both loci was found to be negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has performed extensive genetic studies in PGIA, elucidating the most critical factors of susceptibility to this rheumatoid arthritis-like disease [22]. Genome-wide screening studies, confirmed by testing congenic and interval-specific congenic BALB/c strains, have revealed that numerous chromosome regions (genes) are simultaneously involved in susceptibility to PGIA [22][23][24]. Similar to the conclusion of age-associated human autoimmune disease, while the major histocompatibility complex (MHC) is a critical genetic component, the MHC alone is insufficient to control disease susceptibility [18,25].…”
Section: Discussionmentioning
confidence: 98%